Judge Bias in Labor Courts and Firm Performance - Pierre Cahuc; Stéphane Carcillo; Bérengère Patault; Flavien Moreau (Institute of Labor Economics (IZA), 2020)
Does labor court uncertainty and judge subjectivity influence firms performance? We study the economic consequences of judge decisions by collecting information on more than 145,000 Appeal court rulings, combined with administrative firm-level records covering the whole universe of French firms. The quasi-random assignment of judges to cases reveals that judge bias has statistically significant effects on the survival, employment, and sales of small low-performing firms. However, we find that the uncertainty associated with the actual dispersion of judge bias is small and has a non-significant impact on their average outcomes.
Keywords: J33; J63; J65; 330; firm survival; judge bias; dismissal compensation; employment